2015
DOI: 10.2105/ajph.2014.302218
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Local Immigration Enforcement Policies on the Health of Immigrant Hispanics/Latinos in the United States

Abstract: Fear of immigration enforcement policies is generalized across counties. Interventions are needed to increase immigrant Hispanics/Latinos' understanding of their rights and eligibility to utilize health services. Policy-level initiatives are also needed (e.g., driver's licenses) to help undocumented persons access and utilize these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
266
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(280 citation statements)
references
References 34 publications
12
266
2
Order By: Relevance
“…31 The stress generated by a combination of documentation status, racial and gender discrimination, and barriers to social services likely adversely affects mental health and HIV risk for undocumented Latino/a sexual minorities, although the exact causal relationships remain unclear. [32][33][34] Conversely, the security provided by having legal documentation to live and work in the United States may have positive effects on mental health and HIV risk for this group. To our knowledge, this is the first study to explore these associations among transgender immigrant Latinas.…”
mentioning
confidence: 99%
“…31 The stress generated by a combination of documentation status, racial and gender discrimination, and barriers to social services likely adversely affects mental health and HIV risk for undocumented Latino/a sexual minorities, although the exact causal relationships remain unclear. [32][33][34] Conversely, the security provided by having legal documentation to live and work in the United States may have positive effects on mental health and HIV risk for this group. To our knowledge, this is the first study to explore these associations among transgender immigrant Latinas.…”
mentioning
confidence: 99%
“…Anecdotal information suggests that Hispanic persons have experienced disrespect and poor-quality health care in Forsyth County; however, with the exception of the Rhodes work cited earlier [2], few formal studies have documented this phenomenon, even at the state level. Despite lack of data, we believe that the historical treatment of other vulnerable and marginalized populations-such as low-income non-Hispanic blacks and whites in North Carolina who experienced the eugenics program [27] many decades before widespread Hispanic/Latino immigration-remains germane to current distrust among the vulnerable Hispanic population (particularly undocumented persons).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Rhodes and colleagues [2] indicated that fear of immigration enforcement policies is generalized across North Carolina counties among Hispanics/Latinos and that interventions are needed to increase immigrant Hispanics' and Latinos' understanding of their rights and eligibility to utilize health services. Hispanic/Latina mothers in the aforementioned study also expressed a profound mistrust of health services, often avoiding such services and even sacrificing the health of their families.…”
mentioning
confidence: 99%
“…Each report-back lasted approximately 2 hours and was conducted in Spanish. We shared data from a previous study by our partnership, including both quantitative data demonstrating that Latina mothers in North Carolina seek prenatal care later and have inadequate care compared to non-Latina mothers and qualitative data describing pro-found fear among Latinos in North Carolina about accessing and utilizing services [12]. We facilitated discussions about addressing these issues by asking participants to respond to 2 main questions: "Which of these findings seem most relevant to you?"…”
Section: Data Collectionmentioning
confidence: 99%
“…Under Section 287(g) and Secure Communities, traffic violations have been the most common charge against arrested immigrants, and the number of immigrants arrested for driving without a license has increased [31]. Given the threat of being stopped by local police who may be involved in immigration enforcement, many Latinos in North Carolina are reluctant to drive, even for the purpose of seeking needed health services [12].…”
mentioning
confidence: 99%